2022
DOI: 10.1097/mnh.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence as tool for cardiovascular and diabetes risk prediction

Abstract: Purpose of reviewAdvanced glycation endproducts (AGE) have an important role in the development of chronic complications in diabetes mellitus and in renal failure. Skin autofluorescence (SAF) is a simple noninvasive optical technique to estimate AGE levels in the dermis. SAF increases with age, but rises more rapidly in diabetes and renal failure, and is also associated with, and a predictor of their complications. Recent findingsIn recent large population studies, SAF is a strong predictor of development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This follows previous data about SAF's ability to predict complications of DM. Also, in another paper, Smit et al [28] reported SAF to be a simple, non-invasive tool for the evaluation of AGE levels and also in identifying patients with, or at high risk for developing, DM, those at high CV risk, including vascular complications.…”
Section: Prediction Of Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…This follows previous data about SAF's ability to predict complications of DM. Also, in another paper, Smit et al [28] reported SAF to be a simple, non-invasive tool for the evaluation of AGE levels and also in identifying patients with, or at high risk for developing, DM, those at high CV risk, including vascular complications.…”
Section: Prediction Of Dmmentioning
confidence: 99%
“…Additionally, researchers noted an association between skin autofluorescence (SAF) and heightened risk for diverse populations encountering CVEs [21,22]. This relationship between vascular injury and AGEs has been widely studied, and AGEs have been identified as potential indicators of CVEs and fatalities [21,[23][24][25][26][27][28][29][30][31]. A non-invasive technique for quantifying AGEs known as SAF has emerged as a promising instrument for evaluating CV risk.…”
Section: Introductionmentioning
confidence: 99%
“…Skin autofluorescence (SAF) has been shown to be a biomarker of cumulative skin AGEs [ 69 ], and measuring facial fluorescence intensity allows for an assessment of the skin glycation index [ 67 ]. SAF is also a powerful and independent predictor for cardiovascular disease and type 2 diabetes (T2D) [ 70 ]. Most compounds on the cosmetic market focus on blocking or reversing the initial saccharification reaction, i.e., the binding between proteins and sugars, reducing the formation of early saccharification Amadori products [ 71 ].…”
Section: The Hazards Of Skin Glycationmentioning
confidence: 99%